Fagiolina del Trasimeno, an Italian cowpea landrace: effect of different cooking techniques and domestic storage on chemical and biological features. (5th August 2022) - Acito, Mattia; Palomba, Martina; Fatigoni, Cristina; Villarini, Milena; Sancineto, Luca; Santi, Claudio; Moretti, Massimo
Summary: The aim of this work was a chemical and biological characterisation of Fagiolina del Trasimeno (Italian cowpea landrace) in its coloured and white variants. After opening the package (T0 ), samples were addressed to a set of chemical and biological assays. Analyses were also conducted on cooked, 6‐month‐stored (T1 ) and commercial products. Chemical composition was comparatively analysed by nuclear magnetic resonance (NMR) of the proton. At both T0 and T1, raw coloured Fagiolina del Trasimeno showed statistically higher values in terms of phenolic content (T0 : 11.51 mg GAE/g, T1 : 9.34 mg GAE/g) and antioxidant activity (DPPH T0 : 27.40 μmol TE/g, T1 : 20.15 μmol TE/g; ABTS T0 : 37.98 μmol CE/g, T1 : 27.24 μmol CE/g) when compared with white/commercial variants. Globally, boiling, pressure‐cooking, and storage led to a loss in phenolic content and antioxidant activity. However, values in coloured samples generally remained higher than those observed in the other products. Finally, Fagiolina del Trasimeno extracts were shown to inhibit cyclooxygenase activity in HepG2 cells (up to −41.96%). In summary, these results highlighted interesting chemical and biological features of this product, showing the impact of routine procedures, as well. Abstract :